MODEL LIVING QUR’AN MUSLIM MILENIAL BANGKA BELITUNG DI MEDIA SOSIAL - Purwanto, Tinggal; Wahyudi, Wahyudi (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
This study on the model of living Qur'an of millennial Muslims in Bangka Belitung on social media attempts to examine the model of living Qur'an of millennial Muslims in Bangka Belitung formed through social media and to reveal the influence of living Qur'an activities through social media on the religiosity of millennial Muslims in Bangka Belitung. This study is a type of field research that uses a qualitative descriptive research method with a phenomenological approach. The results of this study found that the living Qur'an activities of millennial Muslims in Bangka Belitung on social media vary, both independently and in groups using various applications available on social media. These activities include: memorizing the Qur'an, learning to read the Qur'an, learning to write verses of the Qur'an, learning the tajwid of the Qur'an, learning the interpretation of the Qur'an, training in translating the Qur'an, studying the Qur'an, completing the Qur'an, learning the tilawah/qiro'ah of the Qur'an, and learning the science of the Qur'an. These various activities show that millennial Muslims in Bangka Belitung have been able to adapt to current technological advances. The living Qur'an activity has a majority positive influence on their daily lives and shows differences in perception in responding to and utilizing technological advances in interacting with the Qur'an